The Influencing Factors of the Career Pathway for Health Professions’ Education - Ayesha Naveed, Ayesha Naveed; Barik Ahmed, Ayesha Haque, Amer Siddiq, Huma Farid, Saria Khalid, Barik Ahmed, Ayesha Haque, Amer Siddiq, Huma Farid, Saria Khalid (Journal of Rawalpindi Medical College, 2022)
Objectives: In this study our objective was to identify and explore the factors that influenced the choice of those Medical and Dental Graduates who chose HPE as a sole career, as to our knowledge there is yet to be an attempt exploring the factors influencing the choice of HPE as a sole career. Significance of Study: Doctors and dentists have a wide variety of specialties. One such specialty is HPE that revolves around all three divisions, undergraduate, postgraduate and the continuing professional development, of a Medical and Dental Practitioner. In Pakistan, there is a varied perception of this specialty despite it encompassing the very essence in the journey of a medical and dental graduate, aiming to produce a population of ethical, knowledgeable, skilled and up-to-date professionals. (9-11)To address these, a formal process of training is required with enrollment in an HPE Program. This study has been designed to identify and explore the choice of those Graduates who have opted HPE as a sole career. 1. Materials and methods Study Design: A qualitative exploratory design was employed to explore the factors influencing specialty preference by phenomenology(12) Study Setting and Duration: The study was conducted at Islamic International Medical College, Riphah International University, Islamabad. Data was collected over four months, February to May, and the total duration of the study was from February to June. Study Population: All medical and dental graduates who had completed a post-graduate HPE qualification and had at least five years’ experience. Population size: A total 18 doctors were identified after the inclusion and exclusion criteria. However, only 6 agreed to participate in the study. Inclusion Criteria: Medical and Dental graduates that had opted post-graduate HPE qualification.